Design of tests for mean and variance under complexity-an application to rock measurement data. (June 2021) - Aslam, Muhammad; Bantan, Rashad A.R.; Khan, Nasrullah
Highlights: Existing t -test under classical statistics cannot be applied when the data is uncertain. t -tests under the neutrosophic statistics. Proposed tests for testing the means of single and two neutrosophic populations. Comparison of the proposed tests with the t-tests under classical statistics. Abstract: The student t -test and F-test are applied for testing the hypothesis of the population mean and variance, respectively. The existing t -test and F-test under classical statistics cannot be applied when the data is uncertain, indeterminate, and fuzzy. Neutrosophic statistics is applied when data is indeterminate, uncertain, and vagueness. This paper introduces the t -test and F-test under neutrosophic statistics. The designing of the proposed tests for testing the population means and testing the equality of population variances are presented. The comparison of the proposed tests with the t -test and F-test under classical statistics is also given. A real example from rock engineering is taken for the illustration of the proposed tests. The comparative study shows that the proposed tests are effective, flexible, and informative to be applied in uncertain environment.